Knowledge and Experience in Shaping Administrator Professionalism: The Role of Information Systems Administration - Said, Abi Hasan; Nursaid; Suharsono, Riyanto Setiawan (Ilomata International Journal of Management, 2026)
In the context of globalization and the rapid advancement of information technology, organizations are mandated to adapt and enhance the quality of their human resources to maintain competitive advantage. This situation has posed challenges to the professionalism of administrators in delivering prompt, accurate, and responsive services to students and faculty members. The professionalism of administrators is substantially influenced by their capacity to manage information effectively and to optimize the utilization of information technology. This study aimed to design and develop an administrative information system that functions as a moderator in the relationship between administrators' knowledge and experience and their professionalism. Primary data were collected from a population of 100 operators responsible for managing the PDDikti system at Jember State Polytechnic, with a total sample size of 100 respondents. Structural Equation Modeling (SEM) was utilized for data analysis employing WarpPLS software. the findings revealed that knowledge and experience exert a positive and significant effect on administrator professionalism. Furthermore, knowledge and experience positively and significantly influenced the administrative information system, which in turn mediated the enhancement of administrator professionalism. This study recommends the improvement of training programs, the development of information systems, and the reinforcement of work experience's role within higher education administration.